Acido (R)-α-lipoico: supplemento nella terapia adiuvante per la prevenzione di complicanze diabetiche - Maglione, Emilia; Marrazzo, Giuseppe (Progress in Nutrition, 2015)
α-Lipoic acid (ALA) has a broad spectrum of activity towards numerous radicals and reactive oxygen species and enhances the endogenous antioxidant systems by promoting the synthesis and/or availability. ALA is considered a powerful natural antioxidant and it is widely used as an adjuvant for the treatment of oxidative stress-dependent pathologies (eg. nerve pain associated with peripheral neuropathies with different etiology). The low bioavailability of ALA limits the therapeutic potential of this antioxidant, when orally administered. To overcome such a limit, very recently in the scenario of the nutraceutical supplements, a liquid formulation of ALA for oral use (Liponax sol) has been proposed, which is capable of increasing the bioavailability of R-ALA, the natural and the most active enantiomer of ALA. This article describes the effects observed in patients with diabetic neuropathy treated  with the liquid formulation of  R-ALA as an adjuvant therapy. In this study we have assessed the vibration perception threshold, which is the most widely used quantitative sensory testing approach, increases in case of peripheral neuropathies, and is considered a marker for predicting the risk of foot ulceration. We observed that the adjuvant treatment of R-ALA lowers the vibration perception threshold and  reduces the number and intensity of night cramps, thus improving the quality of life of patients. From this study we can conclude that Liponax sol promotes an improvement in function of the neuronal fibers affected in patients with diabetic neuropathy. This study also supports this R-ALA formulation as a treatment for all of those diseases that require chronic antioxidant therapies.